2021
DOI: 10.1038/s41467-021-21684-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace element catalyses mineral replacement reactions and facilitates ore formation

Abstract: Reaction-induced porosity is a key factor enabling protracted fluid-rock interactions in the Earth’s crust, promoting large-scale mineralogical changes during diagenesis, metamorphism, and ore formation. Here, we show experimentally that the presence of trace amounts of dissolved cerium increases the porosity of hematite (Fe2O3) formed via fluid-induced, redox-independent replacement of magnetite (Fe3O4), thereby increasing the efficiency of coupled magnetite replacement, fluid flow, and element mass transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…While the catalytic role of hydrothermal fluids in the marcasite to pyrite transformation requires further detailed studies, it is likely that the rapid transformation is due to CDR mineral replacement reactions rather than solid-state transformation. This is because at low temperatures, CDR is much faster than solid-state reactions, as has been demonstrated in numerous hydrothermal mineral phase transformations in sulfides, , tellurides, , phosphates, , carbonates, oxides, , and silicates. , …”
Section: Discussionmentioning
confidence: 97%
“…While the catalytic role of hydrothermal fluids in the marcasite to pyrite transformation requires further detailed studies, it is likely that the rapid transformation is due to CDR mineral replacement reactions rather than solid-state transformation. This is because at low temperatures, CDR is much faster than solid-state reactions, as has been demonstrated in numerous hydrothermal mineral phase transformations in sulfides, , tellurides, , phosphates, , carbonates, oxides, , and silicates. , …”
Section: Discussionmentioning
confidence: 97%
“…2C, 6A), is consistent with the preservation of external shape and dimensions during pseudomorphic replacement (Putnis, 2009). At temperatures below 300°C (the upper temperature limit for CD-type deposits, e.g., Wilkinson, 2013), mineral replacement occurs via coupled dissolution-reprecipitation reactions (CDR), which can result in positive feedbacks that are integral for ore formation (e.g., Xing et al, 2021). In the following discussion, we evaluate the reactions involved in hydrothermal fluid flow through the host rock and use mineralogical constraints to determine the local evolution of pH and fO 2 during fluid-rock interaction.…”
Section: Discussionmentioning
confidence: 99%
“…, monazite). 31–36 It is identified as a late-stage secondary mineral. 2,31,37,38 For example, A. Mahmoud and Williams-Jones 31 suggested that cerianite is the product of the weathering of minerals containing light REEs such as monazite and bastnasite in their studied granitic batches from Egypt.…”
Section: Introductionmentioning
confidence: 99%